Blockchain-Based Traceable Multi-Level Revocation Attribute-Based Encryption - Zhigang Xu; Tiantian Pan; Hongmu Han; Xinhua Dong; Zhongpeng Wang; Miaomiao He (IEEE Access)
With the development of cloud computing and big data, data security and privacy protection in multi-user environments have become particularly important. Existing encryption schemes exhibit significant deficiencies in addressing the flexible revocation of user attributes and dynamic changes in access permissions, leading to unauthorized users illicitly accessing and tampering with data. Therefore, we propose a Blockchain-based Traceable Multi-Level Revocable Attribute-Based Encryption Scheme (BTMAR-ABE). This scheme combines the advantages of Attribute-Based Encryption (ABE) technology and blockchain, achieving real-time attribute updates and verification through smart contracts, thereby avoiding reliance on a single centralized management server and introducing uniquely associated random numbers to prevent collusion attacks. To achieve flexible and secure data access control, we designed a multi-level revocation mechanism for both temporary and permanent revocation to address short-term and long-term permission change requirements. Performance evaluation and security analysis indicate that the BTMAR-ABE scheme can effectively resist chosen plaintext attacks, attribute revocation attacks, and collusion attacks, while demonstrating significant efficiency advantages in computational cost. Simulation results further demonstrate that this scheme has high practical value in data security and access control.